The composition design of MOF-derived Co-Fe bimetallic autocatalysis carbon nanotubes with controllable electromagnetic properties. (December 2020) - Yan, Jing; Huang, Ying; Yan, Yonghui; Zhao, Xiaoxiao; Liu, Panbo
Abstract: MOF-derived magnetic carbon nanotubes microwave absorbers have been prepared by some researchers, but how to control the length and quantity of MOF-derived carbon nanotubes is still a big challenge. In this work, the number and length of carbon nanotubes were regulated by introducing Fe atoms into the bimetallic Zn-Co MOFs and optimizing the composition proportion of Zn 2+ and Co 2+ in the precursor. When the molar ratio of Zn 2+ and Co 2+ was 1:1, the carbon nanotubes was most; When changed to 6:1, the obtained absorbers possess not only strong absorption capability but also wide absorption bandwidth only under 15 wt% filling loading. The excellent performance ascribed to the strong interfacial polarization and impedance matching. The dielectric loss mainly resulted from the conductive network formed by a suitable number of long carbon tubes. We believe that this research will provide a necessary reference for future MOFs-derived magnetic carbon nanotubes microwave absorbers.